Laminated film, optical member, and image display device

By adopting a three-layer structure in the laminated film of the organic EL display device, the difference between the solubility parameters between the hard coating layer and the first resin layer is set to 1.5 or more, the problem of easy cracks during buckling is solved, and the double improvement of hard coating and buckling is achieved.

CN120171148APending Publication Date: 2025-06-20NITTO DENKO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411858200.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-20
Filing Date
2024-12-17
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The laminated film used in the conventional organic EL display device with excellent buckling properties is prone to cracks when buckled.

Method used

A laminated film with a three-layer structure including a base material, a hard coating layer, a first resin layer and a second resin layer is used, and the difference between the solubility parameters between the hard coating layer and the first resin layer is set to 1.5 or more to suppress the formation of the compatible layer and improve buckling properties.

Benefits of technology

A laminated film with excellent hard coating properties and high buckling properties is realized, and cracks can be suppressed during buckling, thereby improving the durability of the display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120171148A_ABST
    Figure CN120171148A_ABST
Patent Text Reader

Abstract

Provided is a laminated film which has excellent hard coating properties and excellent buckling properties, and which is capable of suppressing the occurrence of cracks even when buckling. A laminated film according to an embodiment of the present invention is provided with a substrate and a hard coat layer disposed on one surface of the substrate. The base material includes a first resin layer and a second resin layer in this order from the hard coat layer side. The difference between the solubility parameter of the hard coat layer and the solubility parameter of the first resin layer is 1.5 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated film, an optical member, and an image display device. Background Art

[0002] Image display devices typified by liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices) are rapidly spreading. In organic EL display devices, there is an increasing demand for improved flexibility such as flexibility to bend softly, foldability to be folded, and bendability to be bent.

[0003] On the other hand, on the visual recognition side of a display device, a hard coat may sometimes be provided to prevent scratches, breakage, etc. In this case, a laminated film having a substrate and a hard coat is typically used.

[0004] Prior Art Documents

[0005] Patent Documents

[0006] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2022-118916 Summary of the Invention

[0007] Problems to be Solved by the Invention

[0008] However, when the laminated film (hard coating film) used in an organic EL display device that requires flexibility is bent, cracks may sometimes occur.

[0009] An object of the present invention is to provide a laminated film having excellent hard coatability, excellent flexibility, and capable of suppressing the generation of cracks even when bent.

[0010] Means for Solving the Problems

[0011] [1] The laminated film according to an embodiment of the present invention includes a substrate and a hard coat disposed on one surface of the substrate. The substrate includes a first resin layer and a second resin layer in this order from the hard coat side. The difference in solubility parameter between the hard coat and the first resin layer is 1.5 or more.

[0012] [2] In the laminated film according to the above [1], the second resin layer may be directly disposed on the first resin layer.

[0013] [3] In the laminated film according to the above [1] or [2], the hard coat may be directly disposed on the first resin layer.

[0014] [4] In the laminated film according to any one of the above [1] to [3], the difference in glass transition temperature between the first resin layer and the second resin layer may be 40°C or less.

[0015] [5] The laminated film according to any one of [1] to [4] above, wherein the second resin layer may also contain a polycarbonate resin. The polycarbonate resin may also contain a structural unit derived from a dihydroxy compound. The dihydroxy compound may also be at least one compound selected from the group consisting of isosorbide, isomannitol, and isoidide.

[0016] [6] The laminated film according to any one of [1] to [5] above, wherein the first resin layer may also contain a polycarbonate resin. The polycarbonate resin in the first resin layer substantially does not contain a structural unit derived from a dihydroxy compound selected from the group consisting of isosorbide, isomannitol, and isoidide.

[0017] [7] The laminated film according to any one of [1] to [6] above, wherein the thickness of the first resin layer may also be less than the thickness of the second resin layer.

[0018] [8] The laminated film according to any one of [1] to [7] above, wherein the thickness of the first resin layer may also be 0.5 μm or more and 10 μm or less.

[0019] [9] The laminated film according to any one of [1] to [8] above, wherein the thickness of the second resin layer may also be 15 μm or more and 40 μm or less.

[0020]

[10] An optical member according to another aspect of the present invention includes the laminated film according to any one of [1] to [9] above and an optical film.

[0021]

[11] The optical member according to

[10] above, wherein the optical film includes a polarizer.

[0022]

[12] An image display device according to another aspect of the present invention includes the laminated film according to any one of [1] to [9] above.

[0023]

[13] An image display device according to another aspect of the present invention includes the optical member according to

[10] or

[11] above.

[0024] Advantages of the Invention

[0025] According to an embodiment of the present invention, a laminated film having excellent hard coatability and excellent flexibility and capable of suppressing crack generation even when bent can be realized. Brief Description of the Drawings

[0026] Figure 1 is a schematic cross-sectional view of a laminated film according to an embodiment of the present invention.

[0027] Description of Reference Numerals

[0028] 1 Stacked film

[0029] 10 Hard coat

[0030] 20 Substrate

[0031] 21 First resin layer

[0032] 22 Second resin layer Detailed implementation mode

[0033] Hereinafter, representative implementation modes of the present invention will be described, but the present invention is not limited to these implementation modes. In addition, in order to make the description clearer, compared with the implementation modes, the widths, thicknesses, shapes, etc. of each part are sometimes shown schematically in the drawings, but this is only an example and does not limit the interpretation of the present invention. In this specification, "A and / or B" means any one of "A", "B", and "A and B".

[0034] A. Overall structure of the stacked film

[0035] Figure 1 is a schematic cross-sectional view of a stacked film according to an embodiment of the present invention. The illustrated stacked film 1 includes a hard coat 10 and a substrate 20. The hard coat 10 is disposed on one surface of the substrate 20. The substrate 20 includes a first resin layer 21 and a second resin layer 22, and the first resin layer 21 is disposed on the hard coat 10 side. That is, the stacked film 1 sequentially includes a hard coat 10, a first resin layer 21, and a second resin layer 22. In the stacked film 1, the difference in solubility parameter between the hard coat 10 and the first resin layer 21 is 1.5 or more.

[0036] The stacked film according to the embodiment of the present invention can maintain high hard coatability as a hard coating film, can achieve high flexibility during bending, and can suppress the generation of cracks even when bent.

[0037] In the past, in a stacked film having a hard coat, there has been a problem that it is difficult to balance hard coatability and flexibility. The conventional stacked film used for hard coating films is formed of a two-layer structure of a substrate and a hard coat. Even if a substrate with excellent flexibility is used in such a two-layer structure stacked film, cracks may sometimes occur when bent.

[0038] The inventors have conducted in-depth research and found that the cracks generated in the above-mentioned stacked film can be attributed to a compatible layer formed at the interface between the substrate and the hard coat. The compatible layer is a layer in which the components of the substrate and the hard coat are mixed and present, and the mechanical strength is insufficient. As a result, when the stacked film is bent, cracks can occur starting from the compatible layer.

[0039] Therefore, in order to suppress the generation of the above-mentioned compatible layer, the inventors continued in-depth research and thus completed the stacked film according to the embodiment of the present invention.

[0040] That is, with respect to the laminated film of the embodiment of the present invention, a three-layer structure of a substrate including a first resin layer and a second resin layer and a hard coat is formed, and the difference in solubility parameter between the hard coat and the first resin layer disposed on the hard coat side is set to 1.5 or more. By setting such a configuration, the formation of a compatible layer can be suppressed between the hard coat and the substrate (substantially the first resin layer). Furthermore, the first resin layer sandwiched between the hard coat and the second resin layer can also function as a protective layer for protecting the second resin layer. As a result, the laminated film of the embodiment of the present invention can maintain high hard coatability, and the flexibility is improved, and even when bent, the generation of cracks can be suppressed. It should be noted that such a mechanism is only speculation, does not limit the present invention, and is not subject to a limiting interpretation.

[0041] In this specification, the "difference in solubility parameter between the hard coat and the first resin layer" is the absolute value of the difference in solubility parameter between the hard coat (the material forming the hard coat) and the first resin layer (the material forming the first resin layer). The solubility parameter is the square root of the molecular cohesive energy density, and is also represented as δ. Specifically, when the molar volume is represented as V and the cohesive energy per mole is represented as ΔE, the solubility parameter δ of a certain substance is defined by the following formula.

[0042] δ = (ΔE / V) 1 / 2

[0043] The solubility parameter is sometimes also referred to as the sp value. The unit of the sp value is MPa 1 / 2 The sp value of the hard coat and the sp value of the first resin layer are calculated based on the sp value calculation method of Fedors.

[0044] In the laminated film of the embodiment of the present invention, the hard coat can be directly disposed on the first resin layer. If such a configuration is adopted, the laminated film of the embodiment of the present invention can maintain high hard coatability, and since the formation of a compatible layer is suppressed as described above, high flexibility can be maintained well. The "directly disposed" in this case means that there is no adhesive layer (adhesive layer or binder layer) sandwiched between the first resin layer and the hard coat.

[0045] In the laminated film of the embodiment of the present invention, the first resin layer can be directly disposed on the second resin layer. If such a configuration is adopted, the laminated film of the embodiment of the present invention can maintain high hard coatability, and more excellent flexibility can be achieved. Furthermore, if such a configuration is adopted, it can also contribute particularly to the thinning of the laminated film of the embodiment of the present invention. The "directly disposed" in this case means that there is no adhesive layer (adhesive layer or binder layer) sandwiched between the first resin layer and the second resin layer. It should be noted that within the scope not departing from the purpose of the present invention, one or more layers may be sandwiched between the first resin layer and the second resin layer.

[0046] The hard coatability of the laminated film according to an embodiment of the present invention can be evaluated by pencil hardness (scratch hardness (pencil method)). Specifically, the pencil hardness of the surface on the hard coat side in the laminated film according to an embodiment of the present invention is preferably 2H or more, more preferably 3H or more. The pencil hardness can be measured according to JIS K5600 5-4.

[0047] The flexibility of the laminated film according to an embodiment of the present invention can be evaluated by conducting a flexure test. The flexure test is evaluated, for example, by conducting an MIT test according to JIS P 8115. Specifically, it can be evaluated by the number of repetitions until cracks are generated by repeated flexure. The laminated film preferably has flexibility such that no breakage (cracks) is confirmed even when repeated 50,000 times or more, more preferably 100,000 times or more, still more preferably 150,000 times or more, and particularly preferably 200,000 times or more under these conditions.

[0048] The laminated film according to an embodiment of the present invention preferably has restorability after being bent. The restorability after being bent means that it returns to its original state without leaving a crease after being bent. The restorability after being bent is evaluated, for example, by conducting an MIT test according to the above JIS P 8115. Specifically, it can be evaluated by the number of repetitions until a crease is generated after repeated bending. The laminated film preferably has restorability such that it returns to its original state without leaving a crease even when repeated 50,000 times or more, more preferably 100,000 times or more, still more preferably 150,000 times or more, and particularly preferably 200,000 times or more under these conditions.

[0049] The light transmittance of the laminated film according to an embodiment of the present invention is preferably 80% or more, more preferably 85% or more, and still more preferably 90% or more. The light transmittance can be measured according to JIS K 7361-1:1997.

[0050] The haze (haze value) of the laminated film according to an embodiment of the present invention is preferably 5% or less, more preferably 3% or less, and still more preferably 1% or less. The haze can be measured according to JIS K 7136:2000.

[0051] Hereinafter, each component that can constitute the laminated film according to an embodiment of the present invention will be specifically described.

[0052] B. Hard coat

[0053] In this specification, "hard coat" is used as a general term for a hard surface treatment layer having a surface protection function. Therefore, the hard coat includes not only a general hard coat but also an antireflection layer, an anti-adhesion layer, an antiglare layer, and an anti-sticking layer.

[0054] The hard coat can be composed of any suitable material. In the laminated film of the present embodiment, as described above, it is sufficient that the difference in the sp value between the hard coat and the first resin layer in the substrate is 1.5 or more. Therefore, as the material that can form the hard coat, any suitable material can be selected as long as the difference in the sp value from the first resin layer is 1.5 or more. The sp value of the hard coat is the sp value of the material that can form the hard coat. The sp value of the first resin layer is the sp value of the material that can form the first resin layer.

[0055] As the material that can form the hard coat (hereinafter, sometimes referred to as "material for forming hard coat"), typically, thermosetting resins, energy ray (e.g., ultraviolet ray, visible ray, electron ray) curable resins can be cited. As such curable resins, for example, curable compounds having a (meth) acrylate group that cures by heat, light (ultraviolet ray, etc.), or electron ray can be used. It should be noted that in this specification, "(meth) acrylate" means "methacrylate" and / or "acrylate".

[0056] As specific examples of the curable resin, silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiol polyene resins, and acrylates or methacrylates of polyfunctional compounds such as polyols can be cited. They can be used alone or in combination of two or more. As the curable resin, commercially available products can also be used.

[0057] The material for forming the hard coat can also contain, for example, at least one of (meth) acrylic resins, urethane (meth) acrylates, and copolymers of oligomers and monomers having functional groups. As the monomer having a functional group, for example, polyfunctional (meth) acrylates can be cited. The (meth) acrylate is preferably bifunctional or more, more preferably trifunctional or more. As the oligomer having a functional group, for example, curable urethane (meth) acrylate (e.g., sp value 11.25 MPa 1 / 2 ) can be cited.

[0058] In the hard coat (substantially the material for forming the hard coat), based on 100 parts by weight of all the resins for forming the hard coat, a total of 60 parts by weight or more of curable urethane (meth) acrylate and (meth) acrylate of trifunctional or more can be contained. The total amount is preferably 70 parts by weight or more, more preferably 80 parts by weight or more, further preferably 90 parts by weight or more, and particularly preferably 95 parts by weight or more. The total amount can also be 100 parts by weight. That is, the material for forming the hard coat can also be composed entirely of curable urethane (meth) acrylate and / or (meth) acrylate of trifunctional or more.

[0059] Examples of the curable urethane (meth)acrylate include UV-curable urethane acrylate manufactured by Mitsubishi Chemical Corporation (specifically, trade name "UV-1700TL") and trade name "UT-7314" manufactured by Mitsubishi Chemical Corporation. Examples of the polyfunctional (meth)acrylate include trade name "UNIDIC (registered trademark) 17-807" manufactured by DIC Corporation and trade name "M-920" manufactured by Toagosei Co., Ltd.

[0060] The above-mentioned material for forming the hard coat may further contain any suitable additives. Examples of the additives include anti-blocking agents, dispersion stabilizers, thixotropic agents, antioxidants, ultraviolet absorbers, defoaming agents, thickeners, dispersants, surfactants, catalysts, lubricants, antistatic agents, etc. In addition, the above-mentioned material for forming the hard coat may contain any suitable solvent.

[0061] The hard coat can be formed, for example, by coating a material for forming the hard coat on a coating surface (for example, one surface of a substrate (the first resin layer 21 in the illustrated example)) to form a coating layer, and heating (if necessary) and curing the coating layer.

[0062] As a coating method of the material for forming the hard coat, any suitable method can be adopted. Examples include bar coating method, roll coating method, gravure coating method, rod coat method, slot orifice coat method, curtain coating method, fountain coat method, comma coating method.

[0063] The heating temperature of the above-mentioned coating layer can be set to a suitable temperature according to the composition of the material for forming the hard coat. The heating temperature is, for example, 50°C to 150°C.

[0064] As the curing of the above-mentioned coating layer, any suitable curing treatment can be adopted. Typically, the curing treatment is performed by ultraviolet irradiation. The cumulative light amount of ultraviolet irradiation is preferably 100 mJ / cm 2 ~400 mJ / cm 2 .

[0065] The hard coat can also use a resin film made from the material for forming the hard coat. The resin film can be made from any suitable material. In the case of using a resin film, the laminated film of the embodiment of the present invention can be produced by laminating the resin film to the substrate (the first resin layer) through an adhesive layer (for example, an adhesive layer, a binder layer: not shown). It should be noted that the resin film in this case can be selected from any suitable film according to the sp value of the uncured adhesive and the first resin layer (the material forming the first resin layer), and the solvent contained in the adhesive.

[0066] When the hard coat is bonded to the substrate (the first resin layer), the hard coat is formed on an arbitrarily suitable transfer substrate in the same manner as described above. Then, it is bonded to the substrate via an adhesive layer, and thereafter, the transfer substrate is peeled off and removed, completing the transfer onto the substrate (substantially the first resin layer). The laminated film of the embodiment of the present invention can also be produced by such an operation. It should be noted that a compatible layer can be formed at the interface between the adhesive layer and the substrate by the uncured adhesive.

[0067] The thickness of the hard coat is preferably 1 μm or more, more preferably 2 μm or more, further preferably 3 μm or more, and particularly preferably 4 μm or more. The thickness of the hard coat is preferably 10 μm or less, more preferably 8 μm or less, further preferably 7 μm or less, and particularly preferably 6 μm or less. If the thickness of the hard coat is within such a range, the mechanical strength of the laminated film can be improved, and more excellent buckling properties can be imparted to the laminated film.

[0068] C. Substrate

[0069] As described above, the substrate includes the first resin layer and the second resin layer. However, the configuration of the substrate in the laminated film of the embodiment of the present invention is not limited thereto. For example, in the substrate, one or more appropriate layers can be interposed between the first resin layer and the second resin layer, or one or more appropriate layers can be provided on the surface of the second resin layer opposite to the surface on which the first resin layer is disposed. Hereinafter, the first resin layer and the second resin layer will be specifically described representatively.

[0070] C-1. First resin layer

[0071] The first resin layer can be made of a resin material. As described above, the difference in the sp value between the first resin layer and the hard coat is 1.5 or more. Therefore, as the resin material that can form the first resin layer, a material with a difference in the sp value from the hard coat of 1.5 or more can be selected.

[0072] The resin material used to form the first resin layer (hereinafter, sometimes referred to as "the first resin material") can be a material formed of a single resin component or a material (composition) composed of multiple components. When the first resin layer is made of a composition, the solubility sp value of the first resin layer refers to the sp value of the composition as a whole.

[0073] The first resin material is preferably a thermoplastic resin. Specific examples of the first resin material include, for example, (meth)acrylic resins; cellulose resins such as diacetyl cellulose and triacetyl cellulose; cycloolefin resins such as norbornene resins; olefin resins such as polypropylene; polyester resins such as polyethylene terephthalate and polybutylene terephthalate; polyamide resins; polycarbonate resins; and copolymer resins thereof.

[0074] Among them, the first resin material is preferably at least one resin material selected from the group consisting of (meth)acrylic resins, cycloolefin resins, and polycarbonate resins. If the first resin material is at least one of the above, it is particularly easy to adjust so that the difference in sp value between the first resin layer and the hard coat becomes 1.5 or more.

[0075] As the (meth)acrylic resin, any suitable resin can be used. Specifically, the (meth)acrylic resin typically contains, as a main component, repeating units derived from (meth)acrylate monomers having a linear or branched structure. The (meth)acrylic resin may contain repeating units derived from any suitable comonomer corresponding to the purpose. Examples of the comonomer include monomers containing a carboxyl group, monomers containing a hydroxyl group, monomers containing an amide group, (meth)acrylates containing an aromatic ring, and vinyl monomers containing a heterocyclic ring. Examples of commercially available products of specific (meth)acrylic resins include products named HTX-Z (sp value: 9.5 MPa 1 / 2 ) manufactured by KANEKA CORPORATION.

[0076] As the cycloolefin resin, any suitable resin can be used. Specifically, examples of the cycloolefin resin include polyolefins having a cyclic olefin skeleton, and more specifically, polynorbornene. Examples of commercially available products of specific cycloolefin resins include products named ZEONOR (sp value: 8.5 MPa 1 / 2 ) manufactured by ZEON CORPORATION.

[0077] As the polycarbonate resin, any suitable polycarbonate resin can be cited. The polycarbonate resin is a thermoplastic resin having at least one carbonate group (-O=(C=O)-O-) in the molecule. The polycarbonate resin can be synthesized, for example, from a dihydroxy compound and a dialkyl carbonate compound, a diaryl carbonate compound, a diphenyl carbonate compound, etc. Examples of commercially available products of specific polycarbonate resins include products named TARFLON (sp value: 9.7 MPa 1 / 2 ) manufactured by Idemitsu Kosan Co., Ltd.

[0078] When the first resin layer is a polycarbonate resin, the polycarbonate resin preferably substantially does not contain a structural unit derived from at least one dihydroxy compound selected from the group consisting of isosorbide, isomannitol, and isoidide. In this case, in the laminate film, the formation of a compatible layer between the hard coat and the first resin layer can be particularly well suppressed. As a result, it can be particularly helpful for improving the flexibility of the laminate film. In this specification, the above-mentioned "substantially does not contain" means that the proportion of the structural unit derived from the above-mentioned dihydroxy compound in the first resin layer is 1% by mass or less relative to the total weight of the first resin layer. The proportion of the structural unit derived from the above-mentioned dihydroxy compound in the first resin layer is preferably 0.5% by mass or less, more preferably 0% by mass. The total mass of the above-mentioned first resin layer refers to the total amount of all components except volatile components.

[0079] Preferred combinations of the hard coat (substantially a material for forming the hard coat) and the first resin layer (substantially the first resin material) are as follows;

[0080] · Hard coat: HEMA (2-hydroxyethyl methacrylate. sp value 11.25 MPa 1 / 2 ) and the first resin layer: cycloolefin polymer (sp value 8.5 MPa 1 / 2 ), (meth)acrylic resin (sp value 9.5 MPa 1 / 2 ), or polycarbonate resin (sp value 9.7 MPa 1 / 2 );

[0081] · Hard coat: HPA (2-hydroxypropyl acrylate. sp value 11.0 MPa 1 / 2 ) and the first resin layer: cycloolefin polymer (sp value 8.5 MPa 1 / 2 ), or (meth)acrylic resin (sp value 9.5 MPa 1 / 2 ).

[0082] The first resin layer can be a single resin film or a multilayer coextruded film with a second resin layer. When the first resin layer is a single resin film, it can be produced by any suitable forming method. The first resin layer is preferably a film (multilayer coextruded film) formed by multilayer coextrusion with the second resin layer. If it is a multilayer coextruded film, there is no need to provide an adhesive layer between the first resin layer and the second resin layer, and adverse effects caused by the adhesive can be prevented. Furthermore, the first resin layer and the second resin layer (especially the first resin layer) can be thinned.

[0083] The glass transition temperature of the first resin layer is preferably 110 °C or higher, more preferably 115 °C or higher, and still more preferably 120 °C or higher. The glass transition temperature of the first resin layer is preferably 280 °C or lower, more preferably 175 °C or lower, and still more preferably 170 °C or lower. If the glass transition temperature of the first resin layer is within the above range, the processability of the laminated film can be ensured, and the heat resistance can be improved.

[0084] The difference in the glass transition temperature between the first resin layer and the second resin layer is preferably 40 °C or lower, more preferably 38 °C or lower, and still more preferably 35 °C or lower. If the difference in the glass transition temperature between the first resin layer and the second resin layer is within the above range, higher heat resistance and high flexibility of the laminated film can be maintained.

[0085] The thickness of the first resin layer is preferably 10 μm or less, more preferably 7 μm or less, and still more preferably 5 μm or less. The thickness of the first resin layer is preferably 0.5 μm or more, more preferably 1 μm or more. If the first resin layer is produced by coextrusion, thinning that cannot be achieved with a single resin film can be realized.

[0086] The thickness of the first resin layer is preferably less than the thickness of the second resin layer. In this case, the laminated film of the embodiment of the present invention can be thinned, and it can contribute to further improvement in the flexibility of the laminated film.

[0087] C-2. Second resin layer

[0088] The second resin layer can be made of a resin material. The resin material used to make the second resin layer (hereinafter, sometimes referred to as "second resin material") can be a material formed of one resin or a material (composition) composed of multiple components.

[0089] Any suitable material can be used as the second resin material. As specific examples, the same resins as the examples of the first resin material described in item C-1 can be cited. Among them, the second resin material preferably contains a polycarbonate resin. Within the range where the effects of the present invention can be obtained, the polycarbonate resin in the second resin material can have the same composition as the polycarbonate resin described in item C-1.

[0090] In the laminate film of an embodiment of the present invention, it is preferable that the second resin layer contains a polycarbonate resin, and more preferably, the second resin layer contains a polycarbonate resin different from the polycarbonate resin that can be used in the first resin layer. When the second resin layer contains a polycarbonate resin different from the polycarbonate resin that can be used in the first resin layer, the polycarbonate resin in the second resin layer preferably contains a structural unit derived from a dihydroxy compound. The dihydroxy compound preferably contains at least one structural unit derived from a dihydroxy compound selected from the group consisting of isosorbide, isomannitol, and isoidide. If it has such a configuration, the flexibility of the laminate film of the embodiment of the present invention can be significantly improved. Isosorbide, isomannitol, and isoidide are in a relationship of stereoisomers of the structure shown in the following formula (1).

[0091] [Chemical formula 1]

[0092]

[0093] In the polycarbonate resin, the dihydroxy compound particularly preferably contains isosorbide among isosorbide, isomannitol, and isoidide. That is, the second resin layer particularly preferably contains a structural unit derived from isosorbide. If it has such a configuration, the flexibility of the laminate film of the embodiment of the present invention can be particularly significantly improved. Moreover, since isosorbide is obtained by dehydrating and condensing sorbitol produced from various starches that are abundantly present as resources and can be easily obtained, it is excellent in terms of ease of acquisition and production, optical properties, and moldability.

[0094] The polycarbonate resin in the second resin layer preferably has a structure shown in the following formula (2).

[0095] [Chemical formula 2]

[0096]

[0097] In formula (2), n and m are each a positive number of 1 or more. In formula (2), R is a residue of a dialkyl carbonate compound and / or a diaryl carbonate compound.

[0098] Details of the polycarbonate resin that can be suitably used in the second resin material and its production method are described, for example, in Japanese Unexamined Patent Application Publication No. 2014-10291 and Japanese Patent No. 5528606, and this description is incorporated herein by reference.

[0099] In the second resin layer, the proportion of the structural unit derived from the above dihydroxy compound is preferably 20% by mass or more, more preferably 30% by mass or more, still more preferably 40% by mass or more, and may be 100% by mass, for example, relative to the total mass of the second resin layer. The proportion of the structural unit derived from the above dihydroxy compound is preferably 70% by mass or less, more preferably 60% by mass or less, still more preferably 50% by mass or less, relative to the total weight of the second resin layer. The total mass of the above second resin layer refers to the total amount of all components except volatile components.

[0100] The second resin layer may be a single resin film or a multilayer coextruded film with the first resin layer. In the case where the second resin layer is a single resin film, it can be produced by any suitable forming method. The second resin layer is preferably a multilayer coextruded film with the first resin layer. If it is a multilayer coextruded film, it is not necessary to provide an adhesive layer between the first resin layer and the second resin layer, and adverse effects caused by the adhesive can be prevented. Furthermore, the first resin layer and the second resin layer (especially the first resin layer) can be thinned, and the second resin layer can also function as a support for the thinned first resin layer.

[0101] The glass transition temperature of the second resin layer is preferably 100 °C or higher, more preferably 110 °C or higher, still more preferably 120 °C or higher. The glass transition temperature of the second resin layer is preferably 180 °C or lower, more preferably 170 °C or lower, still more preferably 160 °C or lower. If the glass transition temperature of the second resin layer is within the above range, the processability of the laminated film can be ensured and the heat resistance can be improved. The glass transition temperature of the second resin layer is preferably lower than that of the first resin layer.

[0102] The thickness of the second resin layer is preferably greater than that of the first resin layer. The thickness of the second resin layer is preferably 40 μm or less, more preferably 30 μm or less, still more preferably 20 μm or less. The thickness of the second resin layer is preferably 15 μm or more, more preferably 20 μm or more. In one embodiment, the second resin layer can also function as a support for the first resin layer.

[0103] C-3. Method for manufacturing the substrate

[0104] The substrate in the laminated film of the embodiment of the present invention is preferably manufactured by a multilayer coextrusion method (also called coextrusion molding method). Specifically, the manufacturing of the substrate using the multilayer coextrusion method can be carried out, for example, as follows.

[0105] First, prepare the first resin material and the second resin material. The first resin material can also be in the form of pellets. The same applies to the second resin material.

[0106] Next, the first resin material and the second resin material are introduced into each injection port of the multi-layer extrusion molding apparatus having an injection port for the first resin material and an injection port for the second resin material, and are melted by heating at any suitable temperature. It is also possible to introduce each resin material in a pre-heated and melted state (molten state) into the injection port.

[0107] Next, the first resin material and the second resin material are continuously ejected from each ejection port of the multi-layer extrusion molding apparatus (having an ejection port for the first resin material and an ejection port for the second resin material), and at the same time, are stretched into a predetermined size by a T-die of the multi-layer extrusion molding apparatus, and the first resin material and the second resin material are formed into a laminated film shape to obtain a laminate.

[0108] Next, while transporting the laminate through a roller, the laminate is cooled at any suitable temperature to be cured. Thus, a base material in which the first resin layer and the second resin layer are directly laminated can be obtained.

[0109] D. Method for manufacturing a laminated film

[0110] The laminated film of the embodiment of the present invention can be produced by laminating a hard coat, a first resin layer, and a second resin layer in this order. For example, a base material including a first resin layer and a second resin layer can be produced by the above multi-layer extrusion method.

[0111] Next, a hard coat is disposed on the first resin layer side of the base material including the first resin layer and the second resin layer (that is, the side of the first resin layer opposite to the surface facing the second resin layer). The hard coat is disposed by coating a hard coat forming material on the first resin layer side of the base material by any suitable method, and then curing the coated layer of the hard coat forming material by any suitable curing treatment to form a hard coat as a cured film. Thus, the laminated film of the embodiment of the present invention can be obtained.

[0112] It should be noted that the method for manufacturing the laminated film of the embodiment of the present invention is not limited to the above. The laminated film of the embodiment of the present invention can be produced by any suitable method as long as the hard coat, the first resin layer, and the second resin layer are laminated in this order.

[0113] E. Optical member

[0114] The embodiment of the present invention also includes an optical member using the above laminated film. The optical member of the embodiment of the present invention includes the above laminated film and an optical film.

[0115] As the optical film, any suitable optical film can be cited. The optical film may be a film composed of a single layer or a laminate. Specific examples of the optical film composed of a single layer include a polarizer and a retardation film. Specific examples of the optical film configured as a laminate include a laminate of a polarizing plate (specifically, a laminate of a polarizer and a protective film), a conductive film for a touch panel, a surface treatment film, and a laminate formed by appropriately laminating these optical films composed of a single layer and / or optical films configured as a laminate according to the purpose (for example, a circular polarizer for antireflection, a polarizing plate with a conductive layer for a touch panel).

[0116] F. Image display device

[0117] Embodiments of the present invention also include an image display device using the above laminate film or the above optical member. Therefore, the image display device according to an embodiment of the present invention may include the above laminate film or the above optical member. The image display device according to an embodiment of the present invention preferably includes an image display panel and the above laminate film or the above optical member on the visually recognizable side of the image display panel. In the image display device according to an embodiment of the present invention, a hard coat layer of the laminate film is preferably disposed on the visually recognizable side of the image display panel.

[0118] As the image display device according to an embodiment of the present invention, any suitable image display device can be cited. The image display device is, for example, a liquid crystal display device or an organic EL display device, and preferably an organic EL display device. The laminate film according to an embodiment of the present invention is particularly useful for a flexible, foldable, or bendable organic EL display device. Because in such a case, the effects brought by the embodiments of the present invention become significant.

[0119] It should be noted that the use of the laminate film according to an embodiment of the present invention is not limited to the above, and it can also be applied to any suitable optical device and the like.

[0120] Examples

[0121] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited by these examples.

[0122] 1. Evaluation method

[0123] (1) Hard coatability (scratch hardness (pencil method))

[0124] The pencil hardness of the surface of the hard coat layer side of the laminate film obtained in the examples and comparative examples was measured in accordance with JIS K 5600-5-4.

[0125] (2) Flexure test

[0126] For the MIT test based on JIS P 8115, the flexibility of the laminated films obtained in the examples and comparative examples was evaluated as follows.

[0127] The laminated film (thickness: 0.4 mm) was die-cut into a length of 100 cm and a width of 29 cm to obtain a measurement specimen (sample). The sample was placed in an MIT folding endurance tester (manufactured by TESTER SANGYO Co., Ltd.) and repeatedly folded under the conditions of a temperature of 25°C, a folding (bending) radius of curvature R = 1.5 mm, a folding speed of 30 times per minute, and a load of 9.8 N. The folding was performed with the hard coat on the inside. While checking the number of folds, the state of the laminated film was visually observed and evaluated according to the following criteria.

[0128] A (excellent): No breakage (cracks) were confirmed even after more than 200,000 repetitions.

[0129] B (good): Breakage (cracks) were confirmed after 200,000 repetitions, but no breakage (cracks) were confirmed during repetitions of 150,000 times or more and less than 200,000 times.

[0130] C (medium): Breakage (cracks) were confirmed after 150,000 repetitions, but no breakage (cracks) were confirmed during repetitions of 100,000 times or more and less than 150,000 times.

[0131] D (insufficient): Breakage (cracks) were confirmed after 100,000 repetitions, but no breakage (cracks) were confirmed during repetitions of 50,000 times or more and less than 100,000 times.

[0132] E (poor): Breakage (cracks) were confirmed during repetitions of less than 50,000 times.

[0133] 2. Fabrication of laminated film

[0134] [Example 1]

[0135] As a material for forming the hard coat, a solution of HEMA (2-hydroxyethyl methacrylate) resin (sp value: 11.25 MPa 1 / 2 ) was prepared. As resin materials for forming the first resin layer and the second resin layer, "resin material 1" and "resin material 4" shown in Table 1 were prepared, respectively. The difference in the sp value between the hard coat and the first resin layer is as shown in the column of "Difference in sp value between hard coat and resin layer on which hard coat is disposed" in Table 1.

[0136] "Resin material 1" and "resin material 4" are respectively injected into the inlets of a multi-layer extrusion device equipped with an inlet for the first resin material and an inlet for the second resin material, and a laminate is produced through a T-die of the multi-layer extrusion device. The extrusion is carried out at a barrel temperature of 240°C and an extrusion rate of 4.0 kg / h. Then, it is extruded into a sheet shape using a T-die at 270°C, and then cooled using three rollers at 110°C, 120°C, and 180°C. Thus, a base film (substrate) with an overall thickness of 40 μm (the thickness of the first resin layer is 10 μm: the thickness of the second resin layer is 30 μm) is produced.

[0137] After coating the "material for forming a hard coat" on the first resin layer of the obtained substrate, it is heated under the conditions of 60°C for 1 minute. Then, ultraviolet rays (UVA) are irradiated with a cumulative light amount of 2000 mJ / min to cure the coated film of the material for forming a hard coat, thereby forming a hard coat (thickness 2 μm) on the substrate. Thus, a laminated film is produced.

[0138] For the samples of the produced laminated film, the hard coatability is evaluated by the above-mentioned pencil hardness measurement, and the flexibility is evaluated by conducting a flexure test. The results are shown in Table 1.

[0139] [Examples 2 to 3 and Comparative Example 1]

[0140] Except that the first resin material is changed to the material shown in the column of "first resin layer" in Table 1, a laminated film is produced in the same manner as in Example 1. The obtained laminated film is subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0141] [Comparative Example 2]

[0142] Except that the first resin layer is not formed, a laminated film is produced in the same manner as in Example 1. The obtained laminated film is subjected to the same evaluation as in Example 1. The results are shown in Table 1.

[0143] The details of the materials shown in Table 1 are as follows.

[0144] · Resin material 1: Acrylic resin (product name HTX-Z by KANEKA Corporation). Sp value: 9.5 MPa 1 / 2 . Glass transition temperature: 128°C

[0145] · Resin material 2: Cycloolefin resin (product name ZEONOR by ZEON CORPORATION). Sp value: 8.5 MPa 1 / 2 . Glass transition temperature: 163°C.

[0146] · Resin material 3: Polycarbonate resin (product name TARFLON by Idemitsu Kosan Co., Ltd.). Sp value: 9.7 MPa1 / 2 。Glass transition temperature: 150 °C.

[0147] · Resin material 4: Polycarbonate resin. sp value: 10.5 MPa 1 / 2 。Glass transition temperature: 130 °C. Resin material 4 is prepared as follows.

[0148] Charge 37.5 parts by mass of isosorbide (ISB), 91.5 parts by mass of 9,9 - [4 - (2 - hydroxyethoxy)phenyl]fluorene (BHEPF), 8.4 parts by mass of polyethylene glycol (PEG) with an average molecular weight of 400, 105.7 parts by mass of diphenyl carbonate (DPC), and 0.594 parts by mass of cesium carbonate (0.2 mass% aqueous solution) as a catalyst into a reaction vessel. Under a nitrogen atmosphere, as the first - stage process of the reaction, set the heat - medium temperature of the reaction vessel to 150 °C, and dissolve the raw materials with stirring as needed (about 15 minutes).

[0149] Next, set the pressure inside the reaction vessel to normal pressure to 13.3 kPa, and while raising the heat - medium temperature of the reaction vessel to 190 °C over 1 hour, draw out the generated phenol outside the reaction vessel.

[0150] After maintaining the temperature inside the reaction vessel at 190 °C for 15 minutes, as the second - stage process, set the pressure inside the reaction vessel to 6.67 kPa, raise the heat - medium temperature of the reaction vessel to 230 °C over 15 minutes, and draw out the generated phenol outside the reaction vessel. Since the stirring torque of the stirrer gradually increases, heat it up to 250 °C over 8 minutes. Further, in order to remove the generated phenol, reduce the pressure inside the reaction vessel to 0.200 kPa or less. After reaching the specified stirring torque, end the reaction, extrude the generated reaction product into water, and then perform pelletization to obtain a polycarbonate resin containing structural units derived from dihydroxy compounds in a ratio of BHEPF / ISB / PEG = 42.9 mol% / 52.8 mol% / 4.3 mol%.

[0151] Table 1

[0152]

[0153] As shown in Table 1, it is found that for the laminated film of the embodiment of the present invention in which the difference in solubility parameter (sp value) between the hard coat and the first resin layer is 1.5 or more, the hard - coatability and buckling properties are excellent.

[0154] Industrial applicability

[0155] The laminated film of the embodiment of the present invention can be suitably used for optical members such as polarizing plates and image display devices such as organic EL devices.

Claims

1. A laminate film comprising a substrate and a hard coating layer disposed on one surface of the substrate, The substrate includes a first resin layer and a second resin layer in order from the hard coating layer side, The difference in solubility parameter between the hard coat layer and the first resin layer is 1.5 or more.

2. The laminated film according to claim 1, wherein The second resin layer is directly disposed on the first resin layer.

3. The laminated film according to claim 1, wherein The hard coating layer is directly disposed on the first resin layer.

4. The laminated film according to claim 1, wherein The difference in glass transition temperature between the first resin layer and the second resin layer is 40° C. or less.

5. The laminated film according to claim 1, wherein The second resin layer comprises a polycarbonate resin. The polycarbonate-based resin comprises a structural unit derived from a dihydroxy compound, The dihydroxy compound is at least one compound selected from the group consisting of isosorbide, isomannide and isoidide.

6. The laminated film according to claim 1, wherein The first resin layer includes a polycarbonate resin. The polycarbonate-based resin does not substantially contain a structural unit derived from a dihydroxy compound selected from the group consisting of isosorbide, isomannide, and isoidide.

7. The laminated film according to claim 1, wherein The thickness of the first resin layer is smaller than the thickness of the second resin layer.

8. The laminated film according to claim 7, wherein The thickness of the first resin layer is 0.5 μm or more and 10 μm or less.

9. The laminated film according to claim 8, wherein The second resin layer has a thickness of 15 μm or more and 40 μm or less. 10 . An optical member comprising the laminated film according to claim 1 and an optical film.

11. The optical component according to claim 10, wherein The optical film includes a polarizer. 12 . An image display device comprising the laminated film according to claim 1 . 13 . An image display device comprising the optical member according to claim 10 .

Citation Information

Patent Citations

  • Transmission system of subscriber line

    JP1980028606A

  • Circularly polarizing plate and display device

    JP2014010291A

  • Surface protective film and display device using surface protective film

    JP2022118916A